Advancing the chemistry of phosphole - Ng, Kim Hong (2015)
We have studied the influence of two types of unsaturated substituents on the α-position of the weakly aromatic phospholes. They include the vinyl group and the Fischer carbenes. The presence of this vinylic group has induced linear π-conjugation with the diene unit of phosphole. This has in turn activated the dienic system resulting in a unique chemistry that is rarely (or never) observed in the other 5-membered heteroarene derivatives. Synthesis of the desired 2-vinylphosphole is via 2-formylphosphole which is prepared from 2-lithiophosphole. Then, it is complexed to W(CO)5 and characterised by X-ray analysis. Both the trivalent 2-vinylphosphole and the complexed form are subjected to various cycloaddition reactions. Three reactive sites are created and the cycloaddition pathway selected is exclusive to the specific reagent. Similarly, we started the synthesis of pentacarbonyl tungsten 2-phospholylcarbene derivatives from 2-lithiophosphole. Using the most general entry to Fischer carbenes, trivalent phospholylcarbene and tetravalent phospholylcarbene are obtained. Several trial experiments with the trivalent phosphole-substituted carbene have shown the lone pair on P will disturb the exclusive reaction at the carbenic carbon. Thus, the tetravalent phospholylcarbene became the main focus for the study. This complex behaves in the same way as a standard Fischer carbenes when subjected to oxidation and hydrolysis. However, a completely different picture emerged from the reaction with neat styrene and alkynes.